(untitled) - Massarella, Derek (New Haven, 1990)
This book consists of the following many parts: first encounters with Japan, striking out the english and the age of reconnaissance, the east India company reaches Japan, first years in Japan, hopes illusions and disappointment, living and surviving in hirado, the manila voyages and withdrawal from Japan, further attempts at direct trade after 1623.
Keywords: East india company; History